(untitled) (Takwil: Journal of Quran and Hadith Studies, 2026)
Chronological interpretation of the Qur’an (tafsīr nuzūlī) has evolved through the interaction between the Islamic exegetical tradition and modern historical approaches. Nevertheless, the intellectual position of Muḥammad ‘Ābid al-Jābirī within this development has not been comprehensively examined. This article aims to analyze the intellectual position and methodological characteristics of al-Jābirī’s tafsīr nuzūlī within contemporary Qur’anic exegesis. Employing a qualitative library research design with a historical-comparative approach, the study draws primarily on Madkhal ilā al-Qur’ān al-Karīm and Fahm al-Qur’ān al-Ḥakīm, complemented by relevant scholarship on Qur’anic chronology, tafsīr nuzūlī, and contemporary Qur’anic interpretation. The analysis identifies the methodological features of al-Jābirī’s exegesis, compares them with earlier chronological commentaries, and maps their relationship to broader developments in contemporary tafsir. The findings demonstrate that al-Jābirī reformulates tafsīr nuzūlī by synthesizing classical exegetical reports, historical inquiry, and the framework of qirā’ah mu‘āṣirah. Unlike earlier chronological exegetes, he develops an ijmālī-mawḍū‘ī structure with a tārīkhī-falsafī orientation, integrating chronological reading, historical analysis, and the contemporary actualization of Qur’anic meaning. The study further reveals that al-Jābirī occupies a mediating intellectual position by preserving the epistemological foundations of the Islamic exegetical tradition while critically incorporating historical approaches without embracing revisionist assumptions. These findings establish al-Jābirī as a significant contributor to the development of modern tafsīr nuzūlī and advance the conceptual mapping of contemporary Qur’anic exegetical methodology.